Peran Guru Pendidikan Agama Islam dalam Menanamkan Nilai-Nilai Karakter Peserta Didik Sekolah Dasar - Andriani, Eva; Saputro, Agung; Ma’ani, Arifatul (TIN: Terapan Informatika Nusantara, 2023)
The teacher is the main figure who occupies a position and plays an important role in the world of education. Teachers are not only teachers of science, but also have to supervise to help the growth and development of students. "Teachers, especially Islamic religious education teachers, are expected to be able to have and show good personality traits, such as honest, compassionate, helpful, open, patient and so on, therefore teachers are also expected to be able to instill character in students so that they have good character. glorious. The task of a teacher is not easy, especially for Islamic religious education teachers. In accordance with the background described above. The author is interested in researching the extent of the role of Islamic Religious Education Teachers in instilling character values ​​in students at SDN Pasrujambe 08. This type of research is Field Research, namely research that requires researchers to go to the field to make observations about a phenomenon in a natural setting. The data sources used are primary data sources and secondary data sources. Data collection techniques are interviews, observations and documentation. Meanwhile, the data analysis technique used is inductive through data validity, data reduction, data display and conclusion (verification). The conclusion obtained is that the role of Islamic Religious Education teachers is in instilling character values ​​in students by creating a conducive, comfortable and enjoyable classroom atmosphere, always behaving well in front of students and always instilling discipline, independence, responsibility, honesty and religion. The methods used to instill character values ​​can be through exemplary methods, giving appreciation, giving moral messages, teaching manners, being honest and open to mistakes, instilling leadership qualities. Supporting factors in instilling character values ​​are religious activities and additional learning such as showing videos. Meanwhile, inhibiting factors in instilling character values include busy parents and the environment. Furthermore, the solution to overcome obstacles in instilling character values ​​is cooperation between teachers and parents and cooperation between schools and the community.